Exploring Challenges and Obstacles in Psychosocial Rehabilitation for Individuals With Chronic Mental Disorders: A Qualitative Study - Fardin Alipour; Zoleikha Arabkari; Mostafa Mardani; Shokoufeh Ahmadi; Hosein Afsharpouya; Mehrangiz Shoaa Kazemi (University of Social Welfare and Rehabilitation Sciences, 2024)
Objective Individuals with chronic mental disorders face various challenges, which are not merely confined to the individual but also involve family caregivers and specialists in the field. Psychological and social rehabilitation assists in improving the functioning of individuals with mental disorders and facilitates their return to mainstream life. This study aims to investigate the challenges encountered in the rehabilitation process of these individuals. Materials & Methods This study employed a qualitative directional content analysis method. The sample consisted of 13 individuals with chronic mental illnesses, 3 family members, and 6 specialists with experience in patient care. Following ethical approval and obtaining informed consent, in-depth, unstructured interviews were conducted, aligning with the research objectives. Purposeful sampling and maximum diversity strategies were utilized to select and invite participants subjected to in-depth, semi-structured interviews. Data analysis followed Granheim and Lundman's approach. Results The analysis of the interviews revealed that the essence of this study is "striving to respond to weakened identity." The categories and subcategories extracted in this study include social limitations (social exclusion, societal negligence), instability (turbulent lifestyle, family as an overlooked entity, and economic pressures), therapeutic challenges (treatment inconsistency, therapist-related challenges, the complex nature of the illness, and postdischarge concerns), structural and macro challenges (social media neglect, incomplete perspectives, financial and credibility challenges) and loss of agency and volition (identity weakening, lack of balance between independence and support). Conclusion The rehabilitation of individuals with chronic mental disorders faces various challenges at individual, interpersonal, familial, organizational and structural levels. Strengthening the psychological and social aspects of rehabilitation can provide a better and more sustainable basis for treatment for these patients. Enhancing the roles and interventions of psychological and social rehabilitation teams, coordinating therapeutic interventions, supporting the families of patients, socializing behaviors toward these patients and their families, and paying more attention to the psychological and social rehabilitation of patients can result in better short-term and long-term outcomes for various stakeholders involved in the rehabilitation process.